(3aUd aj bhdg (B( (3Udi Gddg Ydjg hSde (B) (3aML BOe ehSis - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe CHh GdYHGS CMeO Hf JjejI aUd ai bhdg Udi Gddg Ydjg hSde aML BOe ehSi deG EMJL Ydjg HGdbOQ hHjGf Cf Pdc ai GdeUGFH dG ai GdPfhH s
(3BNQgG (B:s
(3ceG CeQ Gddg HPdc hCeQ Hg Ndjdg EHQGgje hgcPG bGd ZjQ hGMO ef GdYdeGA efge GHf Ybjd hZjQg hGddg CYde HGdUhGH JeJ GdLhGH GdeHGQc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg eWGdH ddcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs